2010
DOI: 10.1002/ep.10504
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fenton process for decolorization of reactive black 5 from synthetic wastewater: Kinetics and thermodynamics

Abstract: The decolorization and degradation efficiency of the azo dye Reactive Black 5 (RB5) by Fenton system were investigated in this study. The operation parameters such as Fe 21 :H 2 O 2 ratio, pH value, initial concentration of RB5, reaction time, and temperature were examined. Maximum decolorization (99%) and degradation (88% COD removal) efficiencies were achieved at the Fe 21 :H 2 O 2 ratio of 0.05 and pH 3 for 15-min reaction time. The decolorization kinetic of RB5 followed pseudo-second-order reaction kinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 33 publications
(43 reference statements)
1
26
0
Order By: Relevance
“…It was observed that the optimum Fe 31 content is about 0.05 mM and the maximum production of hydroxyl radicals takes place at this content. At high Fe 31 concentrations, decolorization efficiency decreases because of the scavenging effect of excess Fe 21 . In the excess amounts of Fe 21 ion, it can react with hydroxyl radical (Eq.…”
Section: Effect Of Initial Fe 3 Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the optimum Fe 31 content is about 0.05 mM and the maximum production of hydroxyl radicals takes place at this content. At high Fe 31 concentrations, decolorization efficiency decreases because of the scavenging effect of excess Fe 21 . In the excess amounts of Fe 21 ion, it can react with hydroxyl radical (Eq.…”
Section: Effect Of Initial Fe 3 Concentrationmentioning
confidence: 99%
“…Fe 31 can also react with H 2 O 2 (Eqs. 9 and 10) to produce HO 2 Á and Fe 21 resulting in decrease in color removal efficiency.…”
Section: Effect Of Initial Fe 3 Concentrationmentioning
confidence: 99%
“…In the direct anodic oxidation process, it undergoes direct charge transfer reactions between the anode surface and the dye pollutants on metal oxide electrodes (Foti, Gandini, Comninellis, Perret, & Haenni, ; Ghanim & Hamza, ). In the indirect anodic oxidation process, strong oxidants are generated during electrolysis, such as hypochlorite/chlorine (Rajkumar, Song, & Kim, ; Szpyrkowicz et al, ), hydrogen peroxide and its analogues (Chen, ; Song et al, ), Fenton's reagents (Argun & Karatas, ), and ozone (Tizaoui & Grima, ). Through direct and indirect oxidation, decolorization is finally achieved.…”
Section: Introductionmentioning
confidence: 99%
“…and suggest possible reaction mechanisms [7,11,25,26], the applicability of AOPs to real wastewater is still an open issue. Therefore, any hypothesis has to be fully validated by means of experimental tests that must be carried out under conditions which must be as close as possible to the real ones.…”
Section: Introductionmentioning
confidence: 99%